2002
DOI: 10.4049/jimmunol.169.8.4586
|View full text |Cite
|
Sign up to set email alerts
|

Receptors and Signaling Mechanisms Required for Prostaglandin E2-Mediated Regulation of Mast Cell Degranulation and IL-6 Production

Abstract: Mast cells are implicated in the pathogenesis of a broad spectrum of immunological disorders. These cells release inflammatory mediators in response to a number of stimuli, including IgE-Ag complexes. The degranulation of mast cells is modified by PGs. To begin to delineate the pathway(s) used by PGs to regulate mast cell function, we examined bone marrow-derived mast cells (BMMC) cultured from mice deficient in the EP1, EP2, EP3, and EP4 receptors for PGE2. Although BMMCs express all four of these PGE2 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 30 publications
10
108
1
Order By: Relevance
“…1B) of this molecule for further study. As described [17,18], PGE 2 alone failed to stimulate degranulation ( Fig 1B) but it significantly potentiated antigen-induced degranulation in a pertussis toxin (PTX)-sensitive manner (Fig. 1C).…”
Section: Potentiation Of Fcεri-mediated Degranulation Cytokine Produmentioning
confidence: 99%
See 2 more Smart Citations
“…1B) of this molecule for further study. As described [17,18], PGE 2 alone failed to stimulate degranulation ( Fig 1B) but it significantly potentiated antigen-induced degranulation in a pertussis toxin (PTX)-sensitive manner (Fig. 1C).…”
Section: Potentiation Of Fcεri-mediated Degranulation Cytokine Produmentioning
confidence: 99%
“…However, as studies in human mast cells may be complicated by the additional inhibitory responses with GPCRs such as adenosine and PGE 2 [10], we elected to utilize mouse BMMCs for our studies. We screened several GPCR agonists, including S1P, adenosine, MIP1-α, Rantes, and PGE 2 , known to modify mast cell function [10][11][12]14,16,18], for their relative abilities to enhance antigen (DNP-human serum albumin (DNP-HSA))-mediated BMMC activation (Fig. 1A).…”
Section: Potentiation Of Fcεri-mediated Degranulation Cytokine Produmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-4 and IL-5 are the prototypic Th2 cytokines, and IL-12 is the critical inducer of a polarized Th1 response and plays a role in inhibiting Th2 response (101). In addition, PGE 2 also influences Th2-mediated humoral immune response by EP2/4 receptor-driven immunoglobulin class switching to IgE and EP3 receptor-dependent potentiation of mast cell degranulation (14,76). In spite of these in vitro data, it has been suggested that PGE 2 has a bronchoprotective effect in patients with bronchial asthma.…”
Section: Role Of Pge2 In the Pathogenesis Of Asthmamentioning
confidence: 99%
“…7C and D). Together, these data clearly show that overexpression of ICAM-1 can counteract (33,34), it also inhibits cytokine release by macrophages (35). We have shown that the concentration of PGE 2 is a major factor in determining its overall affect upon CD8 þ T-cell responses.…”
Section: Countering Pge 2 Inhibition With Overexpressed Icam-1mentioning
confidence: 65%